Pengaruh Inovasi Produk, Etika Pemasaran Islami, dan Kualitas Layanan Terhadap Loyalitas Konsumen Nadheera Luxury di Jepara - Dela Anggraeni Lucytasari; Mahmudatus Sadiyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to determine the loyalty of Nadheera Luxury consumers in Jepara which is influenced by product innovation, Islamic marketing ethics, and service quality, and evaluate the correlation level of product innovation, Islamic marketing ethics, and service quality to consumer loyalty. The method implemented in the research is a quantitative method with multiple linear test tools. The method used to determine the number of samples in this study was purposive sampling, with the results of 100 respondents as samples. The type of data implemented in the study comes from primary data obtained from questionnaires. The data tests in the study included data quality tests, instrument validity, instrument reliability, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on data processing and analysis that has been carried out, it is found that product innovation significantly and positively affects consumer loyalty, Islamic marketing ethics do not significantly affect consumer loyalty, service quality significantly and positively affects consumer loyalty.